Investigating the significance of coagulation kinetics on maintaining membrane permeability in an MBR following reactive coagulant dosing - Autin, Olivier; Hai, F.; Judd, Simon J.; McAdam, Ewan J. (Elsevier, 2016)
In this study, the impact of kinetically controlled floc growth on sustaining membrane permeability following reactive coagulant dosing was determined using a model particle system. Floc formation was indicated to comprise of two stages following coagulant addition: (i) an initial destabilisation phase which encouraged complexation of protein and polysaccharide; and (ii) entrapment of the coarse model particles (3 µm Firefli™ microspheres) in the polymeric complex during the floc growth phase. Floc growth was characterised by an expected time lag as with conventional flocculation systems and biopolymer aggregation was kinetically favoured. When coagulant was dosed during the filtration cycle, the intermediate biopolymer aggregates (comprised of protein and polysaccharide) were preferentially transported toward the membrane increasing fouling. However, when coagulant was dosed at the onset of filtration, membrane fouling was constrained. It is asserted that by dosing at the onset of filtration: (i) early development of biopolymer aggregation is initiated which inhibits transport of the individual biopolymers to the membrane; and (ii) by dosing coagulant in the absence of a developed polarised layer, formation of biopolymer complexes local to the membrane is obviated. However, when dosing coagulant at the onset of filtration, only limited floc growth occurred which can be explained by the low applied wall shear rate and the absence of a ‘polarised’ region which ostensibly promoted floc growth when coagulant was dosed mid-filtration. Based on results from the model particle system studied, it is proposed that reactive coagulant dosing is best undertaken when: (i) filtration is stopped; (ii) modest shear is applied within the bioreactor to promote coagulant dispersion; and (iii) sufficient contact time is allowed to promote floc growth before commencement of filtration.
Keywords: Membrane performanceenhancer; Membrane bioreactor; Direct visualobservation